2011
DOI: 10.1007/s00382-011-1124-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for decadal scale variability in a simulated Atlantic meridional overturning circulation

Abstract: Variability in the Atlantic Meridional Overturning Circulation (AMOC) has been analysed using a 600-year pre-industrial control simulation with the Bergen Climate Model. The typical AMOC variability has amplitudes of 1 Sverdrup (1 Sv = 10 6 m 3 s -1 ) and time scales of 40-70 years. The model is reproducing the observed dense water formation regions and has very realistic ocean transports and water mass distributions. The dense water produced in the Labrador Sea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 75 publications
7
68
1
Order By: Relevance
“…6c). Because the overturning branch of the Arctic Mediterranean, including entrainment of Atlantic water into the overflows south of the GSR, is estimated to account for approximately 2/3 of the total AMOC (Dickson and Brown, 1994;Medhaug et al, 2012), stability of this northernmost branch of the Atlantic THC is important for sustaining a stable global overturning circulation (e.g. Jungclaus et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…6c). Because the overturning branch of the Arctic Mediterranean, including entrainment of Atlantic water into the overflows south of the GSR, is estimated to account for approximately 2/3 of the total AMOC (Dickson and Brown, 1994;Medhaug et al, 2012), stability of this northernmost branch of the Atlantic THC is important for sustaining a stable global overturning circulation (e.g. Jungclaus et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…8b). The most plausible mechanism supported by most models is that a stronger overturning transports more oceanic heat to high latitudes where more of the sea ice melts (Delworth et al, 1993;Medhaug et al, 2011). Contradicting this, some models surprisingly show more sea ice for stronger AMOC.…”
Section: Discussionmentioning
confidence: 99%
“…Bjerknes (1964) suggested that the decadal to multidecadal climate variations were driven by slow changes in the ocean gyre circulation, while many later studies indicate that the main cause is variations in the AMOC, driven by density fluctuations in the convection regions. The mechanisms suggested for this relationship include variations in the meridional heat and salt transports causing basin scale fluctuations in surface temperatures known as the Atlantic Multidecadal Oscillation (AMO; Delworth and Mann, 2000;Latif et al, 2004;Knight et al, 2005), and the effect heat and salinity anomalies have on the density in the convective regions, and hence the strength of the deep water formation (e.g., Delworth et al, 1993;Marshall et al, 2001;Bentsen et al, 2004;Jungclaus et al, 2005;Medhaug et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bentsen et al, 2004;Jungclaus et al, 2005;Msadek and Frankignoul, 2009;Medhaug et al, 2012;Escudier et al, 2013) suggest that AMOC variability is closely linked to convective mixing in the subpolar North Atlantic, but not strongly related to convective mixing in the Nordic Seas. Using multicenturylong control simulations with 10 coupled climate models, Ba et al (2014), however, find in some of the models significant correlation between AMOC variability and convective mixing in the Nordic Seas.…”
Section: Introductionmentioning
confidence: 99%